The Queen of Sheba in the Sunni Exegetical Tradition - Ismail Lala (Religions, 2022)
Sunni exegetes repeatedly assert the authority of the Qur’an to explain itself, and the authority of the prophetic tradition (ḥadīth) or early interpretations when explanations cannot be found in the Qur’an. Yet the treatment that the Queen of Sheba receives by the exegetes reveals that, contrary to their assertions, they are influenced by and are products of their cultural and social milieux. This leads to increasingly androcentric accretions in the Sunni exegetical tradition that depart noticeably from the plain reading of the text. Early tafsīrs, such as that of Muqātil ibn Sulaymān (d. 150/767), generally remain more faithful to the literal Qur’anic reading and promulgate a highly positive impression of the Queen of Sheba’s character and leadership style. Later commentaries, however, including those of Ibn Jarīr al-Ṭabarī (d. 310/923) and ‘Imād al-Dīn ibn Kathīr (d. 774/1373), inevitably influenced by their time, seem to present a more androcentric interpretation that diminishes the agency of the Queen.